Sowing the Sacred: Mexican Pentecostal Farmworkers in California. By Lloyd Daniel Barba. New York: Oxford University Press, 2022. 349 pp. $ 29.95 paper - Nabhan-Warren, Kristy ca. 20./21. Jh. (Church history, 2024)
Sowing the Sacred: Mexican Pentecostal Farmworkers in California. By Lloyd Daniel Barba. New York: Oxford University Press, 2022. 349 pp. $ 29.95 paper. - Volume 93 Issue 3.